The Development of New Therapies for Human Herpesvirus 6 - Prichard, Mark N. (Curr Opin Virol, 2014)
Human herpesvirus 6 (HHV-6) infections are typically mild and in rare cases can result in encephalitis. A common theme among all the herpesviruses, however, is the reactivation upon immune suppression. HHV-6 commonly reactivates in transplant recipients. No therapies are approved currently for the treatment of these infections, although small studies and individual case reports have reported intermittent success with drugs such as cidofovir, ganciclovir, and foscarnet. In addition to the current experimental therapies, many other compounds have been reported to inhibit HHV-6 in cell culture with varying degrees of efficacy. Recent advances in the development of new small molecule inhibitors of HHV-6 will be reviewed with regard to their efficacy and spectrum of antiviral activity. The potential for new therapies for HHV-6 infections will also be discussed, and they will likely arise from efforts to develop broad spectrum antiviral therapies for DNA viruses.